2021
DOI: 10.2174/1574892816666210422125058
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Epigenetic Reprogramming, Mitochondrial Patterns, Cellular Morphology, and Cytotoxicity after Bee Venom Treatment

Abstract: Background: Bee venom is a promising agent for use in cancer treatment due to its selective cytotoxic potential for cancer cells through apoptotic pathways. However, there is no evidence for changes in epigenome and mitochondrial DNA copy numbers after bee venom application. The purpose of this study was to determine the impact of bee venom on cytosine modifications and mitochondrial DNA copy number variation. Methods: A broad range of methods was applied to elucidate the impact of bee venom on neoplastic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The previous study showed that IC50 values for NIH3T3, MDA-MB-231 and HEPG2 cells were 50 μg/mL, 8 μg/mL and 12 μg/mL, respectively. [25] Bee venom treatment (10μg/ml) induced DNA damage in normal blood cells with increased reactive oxygen species. [26] However, bee venom was shown to protect blood cells from irradiationinduced DNA damage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous study showed that IC50 values for NIH3T3, MDA-MB-231 and HEPG2 cells were 50 μg/mL, 8 μg/mL and 12 μg/mL, respectively. [25] Bee venom treatment (10μg/ml) induced DNA damage in normal blood cells with increased reactive oxygen species. [26] However, bee venom was shown to protect blood cells from irradiationinduced DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, the selective effect of bee venom on cancer cells has been confirmed in metastatic breast cancer and hepatocellular cancer cell lines and the study also showed that cells undergo different patterns of epigenetic reprogramming after bee venom treatment. [25] However, to the best of knowledge, there is no understanding on the cellular mechanisms of bee venom for this selectivity in terms of inducing DNA damage by double strand breaks (DSBs) and altering cytoskeleton, in particular beta actin localisation, in cancer cells compared to normal cells. This study aims to reveal the response of cells against bee venom in terms of inducing DNA damage and repair by H2AX phosphorylation and β-actin location within the cells.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results revealed that BV generated morphological changes in the nucleus of MDA-MB-231 cells, and the exploration of cytosine modification in cancer cells showed that 5′-methylcytosine (5meC), 5′-hydroxymethylcytosine (5hmC) cells decreased rapidly after treatment with BV in MDA-MB-231 cells. And 5′-formlylcytosine (5 fC) and 5′-carboxycytosine (5caC) exhibited a similar increasing and then decreasing process ( Uzuner et al, 2021 ).…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…After 72 h incubation, the cell viability of BESA-2B (normal lung epithelial cells) remained unaffected at MEL concentrations ≤4 μg/ml with some reduction in activity, while the viability of NCI-H441 and A549 cells (lung cancer cells) was significantly affected at 2 μg/ml ( Gao et al, 2018 ). Besides, the Selective Index of NIH3T3 (healthy mouse fibroblast cells) was higher than 3 compared to HepG2 and MDA-MB-231 cells, implying that BV was more selective for both types of cancer cells and that NIH3T3 showed altered cell morphology only when BV was 100 μg/ml ( Uzuner et al, 2021 ). Moreover, Melectin at around 15 μM only slightly inhibited NIH3T3; Concentration below 50 μM caused only 20% erythrocyte lysis, with no significant hemolytic effect ( Liang et al, 2021 ).…”
Section: Toxicity Administration Dose and New Drug Delivery Systemmentioning
confidence: 99%
“…It has also been used for the treatment of such neurological diseases as multiple sclerosis (MS), amyotrophic lateral sclerosis (ALS), Parkinson and Alzheimer's (Hwang et al, 2015). Additionally, antimutagenic, radioprotective, an-Quality affecting factors on honeybee venom tinociceptive, anti-inflammatory and anticancer effects of HBV have been described by many other studies (Varanda & Tavares, 1998;Kim et al, 2003;Lee et al, 2004;Son et al, 2007;Gajski & Garaj-Vrhovac, 2009;Mahmoodzadeh et al, 2013;Kolayli & Keskin, 2020;Uzuner et al, 2021). The pharmaceutical value of HBV has been referred to for its valuable ingredients, including proteins (phospholipase A 2 (PLA2), phospholipase B, hyaluronidase, phosphatase, alpha glucosidase), peptides (apamin, melittin, MCD peptide, secapine, pamine, minimine, adolapine, procamine A and B, protease inhibitor, tertiapine, cardiopep, melittin F), phospholipids, biogenic amines (histamine, dopamine, noradrenalin), amino acids (aminobutyric acid, alpha-amino acids) in addition to sugars, minerals (P, Ca, Mg), and volatile compounds (pheromones) (Bogdanov, 2012).…”
Section: Introductionmentioning
confidence: 99%